Innovative Design and Analysis of an Electrically Small Reconfigurable Antenna for GPS and Blue Tooth Applications - Katireddy, H. R.; Narayana, M. V.; Immadi, G. (Engineering, Technology & Applied Science Research, 2021)
In this paper, an electrically small, planar antenna with broad side radiation pattern is presented. The design contains a dipole and a segmented circular loop which works equivalent to that of a magnetic dipole. A circular patch with slots is used to provide impedance matching. In general, electrically small antennas suffer from narrow bandwidth. In this paper, the reconfigurability of the small antenna for two different applications, 1.5GHz and 2.4GHz, is discussed. This reconfigurability was achieved by using a BAR 64-03W pin diode to adjust the resonant frequency. Two reconfigurable frequency bands were achieved at 1.5GHz and 2.4GHz with broad side radiation patterns.